2019
DOI: 10.2147/cmar.s191653
|View full text |Cite
|
Sign up to set email alerts
|

<p>Repeat procedures for recurrent colorectal liver metastases: analysis of long-term liver regeneration and outcome</p>

Abstract: Background and aim: Repeat hepatectomy is increasingly performed for the management of recurrent colorectal liver metastases (CRLM). The aim of this study was to evaluate long-term functional liver volume (FLV) after a second hepatic procedure and to measure survival outcome. Methods: In this retrospective cohort study, patients treated for recurrent CRLM in the years 2005–2015 at two liver centers were included. Total FLV was calculated before the first procedure and before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Although the items of agreement aimed to cover both patients with and without a history of local therapy for CRLM, the reported evidence mainly focused on the first metastatic episode. Hence, the outcomes are less applicable to patients with distant recurrences in the liver, given the presumed higher complexity of surgical procedures in a previously accessed abdominal cavity and given the often reduced liver remnant volume [101]. One potential shortcoming of our study was the underrepresentation of some professions in the multidisciplinary expert panel (two radiation oncologists, two medical oncologists and one technical physician, compared to 19 surgeons and 21 interventional radiologists), which potentially weakens the generalizability of the agreements.…”
Section: Discussionmentioning
confidence: 95%
“…Although the items of agreement aimed to cover both patients with and without a history of local therapy for CRLM, the reported evidence mainly focused on the first metastatic episode. Hence, the outcomes are less applicable to patients with distant recurrences in the liver, given the presumed higher complexity of surgical procedures in a previously accessed abdominal cavity and given the often reduced liver remnant volume [101]. One potential shortcoming of our study was the underrepresentation of some professions in the multidisciplinary expert panel (two radiation oncologists, two medical oncologists and one technical physician, compared to 19 surgeons and 21 interventional radiologists), which potentially weakens the generalizability of the agreements.…”
Section: Discussionmentioning
confidence: 95%
“…The safety and effectiveness of repeat hepatectomy in selected patients have been reported in several studies. [1][2][3][4][5][6] With proper selection, repeat hepatectomy is considered safe, with similar mortality and morbidity to the initial hepatectomy. In well-selected patients, median OS after second hepatectomy has been reported to range from 32 to 43 months, 2,6,8,17 and 5-year OS rates ranged from 30% to 48%.…”
Section: Discussionmentioning
confidence: 99%
“…In well-selected patients, median OS after second hepatectomy has been reported to range from 32 to 43 months, 2 , 6 , 8 , 17 and 5-year OS rates ranged from 30% to 48%. 3 , 6 , 8 A systematic review and meta-analysis of 22 studies, including 1610 patients, found a median OS after hepatectomy for recurrent disease of 35 months and a 5-year OS of 42%. 6 Notably, the median OS of patients not treated with adjuvant HAIP chemotherapy in our study was 57 months, and the 5-year OS was 47%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Butte et al and Andreou and colleagues reported no difference in effectiveness of surgical results [47,49] and the future liver remnant volume did not differ between patients with and without chemotherapy according to Valdimarsson and colleagues [62]. However, Hallet and colleagues found a more congested and friable liver parenchyma after NAC before repeat local treatment, which may increase the risk of bleeding during surgery [50] (Tables 3 and 4).…”
Section: Complications Quality Of Life and Cost-effectiveness (Import...mentioning
confidence: 92%